Diversity and epidemiology of bovine haemoparasites and their potential arthropod vectors in Peninsular Malaysia - David, Ola-Fadunsin Shola (2017)
Bovine haemoparasites are cosmopolitan in distribution, mainly due to the global nature of the cattle livestock industry, and the abundance and widespread dispersal of their arthropod vectors. These haemopathogens are known to cause substantial economic losses to the cattle industry due to decreased productivity and high mortality rates. In spite of their importance, there remains a dearth of information on the epidemiology of haemoparasitic diseases in many parts of the world. The present study therefore aimed to determine the diversity and epidemiology (prevalence, spatial distribution, occurrence of co-infection and risk factors) of bovine haemoparasites in Peninsular Malaysia, and the diversity, spatial distribution, and temporal dynamics of potential arthropods vectors. Blood samples were collected from 1,045 heads of beef and dairy cattle on 43 farms from six geographical zones in Peninsular Malaysia, and subjected to PCR amplification of species-specific genetic fragments for the detection of the various haemoparasites. Molecular detection revealed the presence of these haemoparasites and their prevalence; Anaplasma marginale (72.6%), Theileria orientalis (49.8%),“Candidatus Mycoplasma haemobos” (47.0%), Babesia bovis(32.5%), Babesia bigemina (30.5%), and Trypanosoma evansi (17.9%). There was no distinct pattern of haemoparasites spatial distribution in the country. The six haemoparasites were present in all the sampled farms except one where infection with T. orientalis and T. evansi were not detected. There was no consistent pattern in the prevalence of cattle haemoparasites according to various epidemiological factors. Our study showed that 92.1% of the total cattle sampled were infected with either one or more species of haemoparasites. Triple haemoparasite species co-infection was the most common. Using multivariable logistic regression, cattle breed and age wereidentified as the most common risk factors for haemoparasites infection among the cattle. To determine the diversity and spatial distribution of potential arthropod vectors, haematophagous flies were trapped in 25 of the sampled farms and ticks were collected from 15 farms. Three types of traps (Nzi, Malaise and Intercept) were deployed on the farms, and flies belonging to seven genera and 36 species [Musca (17 species), Stomoxys (6 species), Tabanus (6 species), Chrysops (4 species), and a species each of Haematopota, Haematobia and Haematobosca] were trapped. Two species of ticks Rhipicephalusmicroplus and Haemaphysalis bispinosa were found to parasitize the cattle. To determine the temporal activity patterns of haematophagous diptera on cattle farms and the efficacy of various trapping methods, two each of the Nzi, Malaise and Intercept traps were set in two selected cattle farms (dairy and beef) over a period of one year, accumulating to 216 trap-days. Five genera of flies from 27 species were caught in both farms. The highest abundance was recorded for Muscacrassirostris (62.4%), followed by Stomoxys indicus (15.6%), M. inferior (12.8%), S. calcitrans (4.2%), M. sorbens (1.0%), M. ventrosa (0.8%), S. sistens (0.8%), M. bakeri (0.8%), M. conducens (0.6%), M. asiatica (0.2%) and T. minimus (0.2%). The other species were caught in small numbers. Diurnal activity of the flies followed variable patterns, but peak activity was common in the late evenings (1900hrs). The Nzi trap proved to be the most efficient in trapping a higher diversity and number of haematophagous flies. There was no significant correlation between climatic variables (rainfall and temperature), and the abundance of diptera on the cattle farms. This present study constituted the first attempt in the country to document the molecular epidemiology and risk factors of bovine haemoparasites, and the diversity and dynamics of their potential arthropod vectors. It is envisaged that the data obtained will afford a clearer understanding of the epidemiology of bovine haemoparasitic diseases in Peninsular Malaysia. This in turn could be used to formulate effective treatment, control and prevention measures to assist in improving the health of local cattle in the country.